Eugenia Po(h)l and the “Little Auschwitz” in Łódź - Czyżewski, Andrzej (Sensus Historiae, 2021)
The article aims to critically reflect on the latest projects commemorating the tragic history of the so-called Youth Camp for Polish children, organized by the Germans during World War II in occupied Łódź. The proposed analysis focuses on two main research problems. The first one is the issue of the history of the camp being entangled in current political climate of Poland, both during the communist regime and after the political transformation of 1989. The second problem is the tension between the communicative memory of the camp victims and the needs of mnemonic actors who shape the social image of Polenjugendverwahrlager in Litzmannstadt (PJVL). The author is interested in finding an answer to the question of to what extent Polish collective memory can absorb the full spectrum of experiences of young victims of the PJVL.